2021
DOI: 10.3389/fnbeh.2021.696577
|View full text |Cite
|
Sign up to set email alerts
|

Brain Network to Placebo and Nocebo Responses in Acute Experimental Lower Back Pain: A Multivariate Granger Causality Analysis of fMRI Data

Abstract: Background and Objective: Placebo and nocebo responses are widely observed. Herein, we investigated the nocebo hyperalgesia and placebo analgesia responses in brain network in acute lower back pain (ALBP) model using multivariate Granger causality analysis (GCA). This approach analyses functional magnetic resonance imaging (fMRI) data for lagged-temporal correlation between different brain areas.Method: After completing the ALBP model, 20 healthy subjects were given two interventions, once during a placebo int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…Numerous studies on pain processing have recognized the activation of S1 and S2 regions and this evidence has led to the understanding that during the processing of nociceptive stimuli, S1 and S2 regions of the brain perceive the sensory features of pain (Coghill et al, 1999;Craig, 2002). Additionally, the ACC and IC, components of the limbic system, found to be activated in most PET or fMRI studies of thermal and mechanical pain, are implicated in the emotional processing of pain (Orenius et al, 2017;Cha et al, 2020;Henderson et al, 2020;Shi et al, 2021). It has been reported that the parietal association area and the prefrontal cortex are involved in the processing of thermal pain and are related to cognitive factors such as memory or stimulus evaluation (Strigo et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies on pain processing have recognized the activation of S1 and S2 regions and this evidence has led to the understanding that during the processing of nociceptive stimuli, S1 and S2 regions of the brain perceive the sensory features of pain (Coghill et al, 1999;Craig, 2002). Additionally, the ACC and IC, components of the limbic system, found to be activated in most PET or fMRI studies of thermal and mechanical pain, are implicated in the emotional processing of pain (Orenius et al, 2017;Cha et al, 2020;Henderson et al, 2020;Shi et al, 2021). It has been reported that the parietal association area and the prefrontal cortex are involved in the processing of thermal pain and are related to cognitive factors such as memory or stimulus evaluation (Strigo et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…When the nocebo occurs, significant changes in brain function are observed; however, no definitive conclusion has been reached. The available evidence is primarily based on human neuroimaging studies of nocebo hyperalgesia, and some brain regions have been suggested to be clearly activated, such as the thalamus, insula, hippocampus, ACC, PAG, amygdala, etc 45–47 . We noted that few studies had examined changes in brain activation in nocebo nausea.…”
Section: Discussionmentioning
confidence: 99%
“…The result implied that SA, similar to VA, could modulate pain emotions in patients with PDM. The studies on SA or phantom acupuncture have concluded that SA can specifically activate DLPFC to provide the placebo effect ( Makary et al, 2018 ; Shi et al, 2021 ). However, this study suggested that SA did not exhibit a placebo effect associated with self-control in pain.…”
Section: Discussionmentioning
confidence: 99%